SISTEM KONTROL TEMPERATUR DENGAN 2 EVAPORATOR UNTUK PENGKONDISIAN LOBSTER - Westari, Dwianti; Maknunah, Jauharotul; Kusuma, Aqib Ridwanul (JURNAL REKAYASA ENERGI, 2025)
Freshwater lobsters (Cherax) are cultivated using freshwater, with an ideal water temperature range of 21 to 28 °C. However, achieving and maintaining this temperature range requires a temperature control system. In this case, several control components are used, including a thermostat, TDR, contactor, and selector switch. The thermostat is employed to automatically regulate water temperature, while the TDR functions to reduce the compressor’s workload during startup and to control the operation of the water circulation pump by delaying cooling before circulation begins. The cooling system, equipped with two evaporators, is capable of reaching the initial temperature within 40 minutes and achieving 21 °C in the subsequent 30 minutes. When the system is turned off, the water temperature rises from 21 to 24 °C within 1 hour and 40 minutes.